Preoperative risk factors and incidence of glaucoma after penetrating keratoplasty - MN, Hemanth Raj; G, Bhanushree; Hulinaykar, Raman M.; V, Vijayanath (International Journal of Clinical Trials, 2014)
Background: Glaucoma following penetrating keratoplasty is one of the serious complications due to its frequency of occurrence, difficulty in diagnosis and management, risk of graft failure and irreversible visual loss due to optic nerve damage. The incidence of glaucoma after keratoplasty varies from 9% to 31% in the early postoperative period and from 18 to 35% in the late postoperative period. The aetiology of this disorder is multifactorial and the clear understanding of the various mechanisms that operate during different time frames following penetrating keratoplasty is essential to chalk out the appropriate management algorithms. Methods: Prospective analysis of 100 consecutive eyes which underwent penetrating keratoplasty during the period from September 2009 to December 2010 at Bangalore West Lions super speciality eye hospital was done. The patients were followed up for a minimum period of 9 months. Results: Out of 100 patients mean age distribution was 47 ± 11 years. Of the 100 patients male 68% and 32 female (32%). Out of 100 eyes 38% of them had vision <6/60, 36% of them had vision between 6//36-6/18 and 26% of them between 6/18-6/6. Raised intraocular pressure was found in 15 out of 100 eyes. Mean raise in intraocular pressure was 29 mmHg ± 1.5 mmHg. Out of 15 patients 4 were steroid responders. Mean time of diagnosis of raised intraocular pressure was 5 ± 9.5 months. Pseudophakic Bullous Keratopathy (PBK) in 5 (33.3%) patients, aphakic bullous keratopathy (ABK) in 3 (20%) patients, graft rejection in 2 (13.3%) patients and one each patient (6.7%) of corneal scar, adherent leucoma, chemical injury and congenital hereditary endothelial dystrophy. Aphakic group was at higher risk compared to the other groups and there was not much difference between the phakic and the pseudophakic group. Conclusions: Post penetrating keratoplasty glaucoma continues to be a clinical problem that can be sight threatening in its clinical outcome. It is mandatory that intraocular pressure is monitored on a regular basis. Recognition of the risk factors namely, indications, graft size, lenticular status & associated surgical procedure with penetrating keratoplasty would help in early diagnosis of post penetrating keratoplasty glaucoma. Most of these cases are amenable to medical management.